Learning Outcomes of e-Learning in Psychotherapy Training and Comparison With Conventional Training Methods: Systematic Review - Kasperi Mikkonen; Eeva-Eerika Helminen; Samuli I Saarni; Suoma E Saarni (JMIR Publications, 2024)
BackgroundMental disorders pose a major public health problem in most western countries. The demand for services for common mental health disorders has been on the rise despite the widespread accessibility of medication. Especially, the supply and demand for evidence-based psychotherapy do not align. Large-scale increase of modern psychotherapy is difficult with current methods of training which are often expensive, time consuming, and dependent on a small number of top-level professionals as trainers. E-learning has been proposed to enhance psychotherapy training accessibility, quality, and scalability. ObjectiveThis systematic review aims to provide an overview of the current evidence regarding e-learning in psychotherapy training. In particular, the review examines the usability, acceptability, and learning outcomes associated with e-learning. Learning outcomes are assessed in different modalities including trainee experiences, knowledge acquisition, skill acquisition, and application of trained content in daily practice. Furthermore, the equivalence of web-based training and conventional training methods is evaluated. MethodsFollowing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a search from Ovid, MEDLINE, PsycINFO, and Scopus databases between 2008 and June 2022 was conducted. Inclusion criteria required studies to describe e-learning systems for psychotherapy training and assess acceptability, feasibility, or learning outcomes. The risk of bias was evaluated for both randomized and nonrandomized studies. Learning outcomes were categorized using the Kirkpatrick model. Effect sizes comparing e-learning and traditional methods were calculated. ResultsThe search yielded 3380 publications, of which 34 fulfilled the inclusion criteria. Positive learning outcomes are generally associated with various e-learning programs in psychotherapy training including trainee satisfaction, knowledge, and skill acquisition, and in application of trained content in clinical practice. Learning outcomes generally show equivalence between e-learning and conventional training methods. The overall effect size, indicating this disparity, was 0.01, suggesting no significant difference. This literature displays a high level of heterogeneity in e-learning solutions and assessment methods. Conclusionse-Learning seems to have good potential to enhance psychotherapy training by increasing access, scalability, and cost-effectiveness while maintaining quality in terms of learning outcomes. Results are congruent with findings related to e-learning in health education in general where e-learning as a pedagogy is linked to an opportunity to carry out learner-centric practices. Recommendations for conducting psychotherapy training programs in blended settings supported by activating learning methods are presented. However, due to the heterogeneity and limitations in the existing literature, further research is necessary to replicate these findings and to establish global standards for e-learning, as well as for the assessment of training outcomes in psychotherapy education. Research is especially needed on the effects of training on patient outcomes and optimal ways to combine e-learning and conventional training methods in blended learning settings.